Determinants of bone density and prevalence of osteopenia among female runners in their second to seventh decades of age. - Gibson, J; Harries, M; Mitchell, A; Godfrey, R; Lunt, M; Reeve, J (2000)
This is a cross-sectional study of spine and hip bone density (BMD) in 124 female athletes, aged 16-68 years, who trained for at least 3 hs/week. The aim was to document the effects of competitive running on BMD in women over a broad age range. Thirty-three subjects, aged <35 years, were currently oligo- or amenorrheic and, of the 50 who were >40 years, and who were now menstruating normally, 13 had previously been oligo- or amenorrheic. Fifty-two women <50 years of age had never had disturbed menses. Twenty-four older women were postmenopausal. Women who had never had menstrual disturbance had significantly increased bone density at the lumbar spine, femoral neck, and femoral trochanter, as compared with young normal European reference data (range from +0.4 population SD or T-score units to +1. 2 units according to measurement site and age group). In contrast, young amenorrheic or oligomenorrheic runners had reduced bone density, particularly at the spine (mean T score < -1.1), whereas older runners who previously had disturbed menses, but were now menstruating normally, had bone densities that were similar to sedentary young controls. Postmenopausal runners had bone density values that differed little from sedentary postmenopausal controls matched for time since menopause, after adjusting for the runners' lower body weight. Bone density outcomes were related to candidate explanatory variables. After taking into account the other variables, age, per se, influenced only the femoral neck and Ward's area. Years since last exposure to estrogen (at premenopausal levels) was an important determinant of bone loss at both hip and spine. Body weight had a beneficial influence on the femoral neck region, whereas (in contrast) height had a positive influence on the lumbar spine. Months of breastfeeding (totaled for all children) had a modest, positive influence, which was larger in the femoral measurement sites. There was no evidence of an effect of calcium intake or percent body fat on BMD at any site independent of these other effects. It is concluded that, with the consistent presence of normal premenopausal estrogen levels, running at least 3 hs/week substantially improves bone density, particularly at the proximal femur. This beneficial effect is reversed in the absence of the consistent past and current presence of normal menstrual function. There was no clear benefit of running seen on BMD in postmenopausal women, but premenopausal veteran athletes who started running after the age of 30 years were not disadvantaged compared with early starters.